Transcriptomic response for revealing the molecular mechanism of oat flowering under different photoperiods - Zhang, Man; Jiang, Yuan; Dong, Haixiao; Shan, Xiaohui; Tian, Juan; Sun, Moke; Ma, Feiyue; Ren, Changzhong; Yuan, Yaping (Frontiers in Plant Science, 2023)
Proper flowering is essential for the reproduction of all kinds of plants. Oat is an important cereal and forage crop; however, its cultivation is limited because it is a long-day plant. The molecular mechanism by which oats respond to different photoperiods is still unclear. In this study, oat plants were treated under long-day and short-day photoperiods for 10 days, 15 days, 20 days, 25 days, 30 days, 40 days and 50 days, respectively. Under the long-day treatment, oats entered the reproductive stage, while oats remained vegetative under the short-day treatment. Forty-two samples were subjected to RNA-Seq to compare the gene expression patterns of oat under long-and short-day photoperiods. A total of 634-5,974 differentially expressed genes (DEGs) were identified for each time point, while the floral organ primordium differentiation stage showed the largest number of DEGs, and the spikelet differentiation stage showed the smallest number. Gene Ontology (GO) analysis showed that the plant hormone signaling transduction and hormone metabolism processes significantly changed in the photoperiod regulation of flowering time in oat.Moreover, Kyoto Encyclopedia of Genes and Genomes (KEGG) and Mapman analysis revealed that the DEGs were mainly concentrated in the circadian rhythm, protein antenna pathways and sucrose metabolism process. Additionally, transcription factors (TFs) involved in various flowering pathways were explored. Combining all this information, we established a molecular model of oat flowering induced by a long-day photoperiod. Taken together, the long-day photoperiod has a large effect at both the morphological and transcriptomic levels, and these responses ultimately promote flowering in oat. Our findings expand the understanding of oat as a long-day plant, and the explored genes could be used in molecular breeding to help break its cultivation limitations in the future.